2000
DOI: 10.1111/j.1574-695x.2000.tb01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel antigen fromStaphylococcus epidermidis

Abstract: A genomic DNA library of Staphylococcus epidermidis NCTC 11047 was constructed, using the Lambda Zap Express cloning vector, and screened with serum collected from a patient with S. epidermidis endocarditis. Sequence analysis of a 30 kDa cloned protein, termed staphylococcal secretory antigen, SsaA, identified a novel protein not previously reported in S. epidermidis. SsaA showed strong homology with two other staphylococcal proteins: SceB from Staphylococcus carnosus and a staphyloxanthin biosynthesis protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The high levels of anti-SsaA antibody observed in the 2D-IB assay were in accordance with the results of a previous study (11). The role of anti-SsaA antibody in pathogenesis is not clearly understood; however, SsaA has been postulated to be involved in biofilm-associated infections (11,52). AzoR was recently proven to play a role in providing resistance to thiol-specific stress (53).…”
Section: Discussionsupporting
confidence: 78%
“…The high levels of anti-SsaA antibody observed in the 2D-IB assay were in accordance with the results of a previous study (11). The role of anti-SsaA antibody in pathogenesis is not clearly understood; however, SsaA has been postulated to be involved in biofilm-associated infections (11,52). AzoR was recently proven to play a role in providing resistance to thiol-specific stress (53).…”
Section: Discussionsupporting
confidence: 78%
“…SsaA is an extracellular protein that has shown to be implicated in pathogenesis. 50 Similarly, two strains from diseased sites have putative esxA genes. EsxA is a virulence factor in S. aureus that has also been identified and shown to be functional in some S. epidermidis strains.…”
Section: Resultsmentioning
confidence: 99%
“…Here we showed that this gene is not involved in staphyloxanthin biosynthesis because its deletion had no effect on staphyloxanthin production. Furthermore, the predicted protein product of orf1 shows sequence similarity to the staphylococcal secretory antigen (13).…”
Section: Resultsmentioning
confidence: 99%